Struktur Bawah Permukaan Pantai Semarang berdasarkan Metode HVSR - Muhammad Irham Nurwidyanto; Muhammad Zainuri; Anindya Wirasatrya; Gatot Yuliyanto (Department of Physics, Sebelas Maret University, 2023)
The aim of this study was to obtain a profile for each depth of the subsurface structure of the Semarang coast based on microtremor data. The acquisition of 109 data points in this study was taken using a single-station microtremor tool in the coastal area of Semarang. This study uses the HVSR method to produce the HV curve, amplification factor (A0) and dominant frequency (f0) which can later be used to find the values of vp, vs and vp/vs at each depth. The results obtained in this study include A0 of 0.13 - 5.96, f0 of 0.13 - 7.47 Hz, vs of 154.42 - 1444.404 m/s, vp of 266.40 - 4758.37 m/s and vp/vs of 1,421 – 28,674. Based on the vs analysis, bedrock begins to appear at a depth of 100 m in the eastern and southern parts of West Semarang District and the southern part of North Semarang District. Classification of hard soil, very dense and soft rock from a depth of 100 m shows that it has covered most of the area of Semarang City. However, there are still several areas that still have a medium soil classification, namely most of the areas of Gayamsari District, Genuk District and Pedurungan District, as well as a small part of the area of North Semarang District, West Semarang District and Central Semarang District. Analysis of vp/vs at a depth of 150 m showed a vp/vs classification with a range of 1.4 - 2 in the study area. However, there are still several areas that still have vp/vs values with a value range of 3 – 3.2, namely in the northern part of West Semarang District, eastern Central Semarang District, eastern South Semarang District, northern East Semarang District, northern Gayamsari District, and the central part of Genuk District.